SPICE modelling-Assisted evaluation of dynamic on-resistance characterization in Schottky p-GaN HEMTs amid synchronous buck transient instabilities - Liu, Xinzhi; Hua, Mengyuan; Shafie, Suhaidi; Radzi, Mohd Amran Mohd; Azis, Norhafiz (Elsevier BV, 2024)
This study addresses the critical gap in dynamic on-resistance characterization for GaN HEMTs within the initial unstable state in a non-isolated DC-DC converter, where the output voltage and currents fluctuate and exhibit overshoots or undershoots before stabilizing to their steady-state values, a domain within solar photovoltaic (PV) Maximum Power Point Tracking (MPPT) implementations which is crucial yet insufficiently examined. The authors present a novel multi-pulse test circuit within a synchronous buck converter configuration, complemented by SPICE simulation. This combination allows for the accurate assessment of clamping circuits' performance during transient states, significantly improving the precision of RDS(ON) measurements in unsteady phases. The approach deviates from conventional methods by merging empirical data with simulation insights to validate the efficacy of clamping circuits. The experimental results affirm the methodology's precision, with the highlighted Circuit V showcasing a marginal deviation of 2.32 % from existing benchmarks. This finding substantiates the method's dependability and practicality contributing to the GaN power electronics field. In addition, this research provides a powerful analytical tool for RDS(ON) evaluation, culminating in the design of a test PCB that synergizes with both simulated and empirical evidence, contributing future research in GaN HEMT power converter applications.